Students’ and Teachers’ Perceptions of an Effective English Language Teacher - Yağcıoğlu, Selden (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The present study mainly aimed to investigate the students‟, instructors‟ and alumni‟s perceptions of an effective English language teacher in the English Language Teaching (ELT) Department at Eastern Mediterranean University (EMU). To this aim, personal qualities, professional qualities, pedagogical skills and classroom behaviors of effective English language teachers as perceived by the students, instructors and alumni were identified. The study was designed as a qualitative and quantitative (i.e. a mixed-type) case study. The participants included 82 undergraduate ELT students (student teachers), 10 instructors and 20 alumni. The data was collected through questionnaires, and semi-structured interviews from three groups of participants. The results of the study showed that the perceptions of each group of participants generally differed from another although some similarities were identified. According to the students and alumni, in order to be an effective English language teacher, professional qualities, pedagogical skills and classroom behaviors are more important than personal qualities. On the other hand, the instructors believed that the combination of all qualities is necessary for being an effective English language teacher. The overall findings of the study revealed that the highly important qualities of an effective English language teacher as perceived by the participants were: being fair, reducing students‟ anxiety, being good at classroom management, knowing students‟ names, correcting students without offending, being encouraging, approachable and patient, teaching speaking skills well, having good knowledge of vocabulary and having correct pronunciation, respectively. Although most of the qualities were perceived important, three qualities which are gender, being young and having lived in an English speaking country, were been perceived slightly important. In the light of the results of the study, some implications for pedagogy and further research are suggested. Keywords: effective teacher, English language, teacher qualities, perceptions

ÖZ : Bu çalışma, Doğu Akdeniz Üniversitesi‟ndeki (DAÜ) İngiliz Dili Eğitimi (İDE) Bölümü öğrencilerinin, öğretim elemanlarının ve mezunlarının, etkili İngiliz dili öğretmeni hakkındaki algılarını incelemeyi hedeflemiştir. Bu bağlamda, öğrencilerin, öğretim elemanlarının ve mezunların algıladıkları etkili İngiliz dili öğretmenini açıklayan kişisel nitelikler, profesyonel nitelikler, pedagojik öğretme becerileri ve sınıf içi davranışlar belirlenmiştir. Bu çalışma, nitel ve nicel yöntemlerin uygulandığı bir olgu çalışması olarak tasarlanmıştır. Katılımcılar, İngiliz Dili Eğitimi Lisans programından toplam 82 öğrenci (öğretmen adayları), 10 öğretim elemanı ve 20 mezundan oluşmaktadır. Çalışmanın verileri üç katılımcı grubundan anketler, ve yarı-mülakatlar yoluyla toplanmıştır. Çalışmanın sonuçları, tüm katılımcı grupların algılarının genel olarak birbirinden farklı olduğunu ancak bazı benzerliklerin de bulunduğunu göstermiştir. Öğrencilere ve mezunlara göre, etkili bir İngiliz dili eğitmeni olabilmek için gerekli olan kişisel niteliklerden çok, profesyonel niteliklere, pedagojik kabiliyetlere ve sınıf içi davranışlara sahip olmak gerekmektedir. Bir diğer yandan, eğitmenler etkili bir İngiliz dili eğitmeni olabilmek için tüm niteliklerin birleşiminin gerekli olduğuna inanmaktadırlar. Çalışmanın genel sonuçlarına göre, etkili bir İngilizce öğretmeni olmak için en önemli olan nitelikler sırasıyla: adil olmak, öğrencilerin kaygılarını azaltmak, sınıf yönetiminde başarılı olmak, öğrencilerin isimlerini bilmek, öğrencilerin hatalarını rencide etmeden düzeltmek, teşvik edici, ulaşılabilir ve sabırlı olmak, konuşma becerilerini iyi öğretebilmek, iyi seviyede kelime bilgisine sahip olmak ve doğru telaffuza sahip olmaktır. Her ne kadar niteliklerin birçoğu pozitif olarak algılansa da, cinsiyet, genç olmak ve İngilizce konuşulan bir ülkede yaşamış olmak nitelikleri negatif olarak algılanmıştır. Çalışmanın bulguları ışığında, bazı pedagojik sezdirimlerde bulunulmuş ve ileriki çalışmalar için bazı öneriler sunulmuştur. Anahtar kelimeler: etkili öğretmen, İngiliz dili, öğretmen nitelikleri, algılar
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language Teacher - Education - Study and Teaching - Eastern Mediterranean University - Cyprus, North; Teachers - Training of - English Language; Teaching - Classroom management - Teachers - Teacher effectiveness; Effective teacher; English language; teacher qualities; perceptions